APPLICATION AND MAINTENANCE OF MOORING ROPES TO AVOID THE DANGER OF BREAKING THE ROPE WHILE STANDING At KMP ATHAYA IN 2022 - Idhil Febriana Rahayu; Arleiny; Muh. Dahri (Jurnal Maritim Malahayati, 2022)
Mooring ropes are the most important factor in docking vessels or loading and unloading activities at The mooring rope serves to tether ships to the dock so that when the ship is carried away by currents, wind or waves. However, there are factors that can cause the mooring rope to break. Factors from the ship itself and from outside the ship. The implementation was carried out for 11 months when carrying out marine practices aboard KMP ATHAYA with a research time of July 2021 to June 2022. Data were obtained directly through interviews in research preparation, data testing, data processing, discussion of research results, conclusions and author suggestions using the method qualitative descriptive research. From the observations, it can be concluded that to prevent the breaking of the mooring line by implementing a mooring plan, urging the crew on guard to always pay attention to the mooring rope when the ship is docking, and perform proper maintenance of the mooring line.